Health Seeking Behavior and Cost of Care of Chronic Dermatophytosis: A Hospital-Based Cross-Sectional Study (Nepal Medical College Journal, 2020)
Recent trend in onslaught of chronic and recurrent dermatophytosis not amenable to conventional dose and duration of antifungal agents has been observed in Nepal and India. The major factor implicated behind this surge is use of over-the-counter fixed drug combination containing topical steroids. This study aimed to examine the health seeking behavior, pattern of drug use and cost of care of chronic dermatophytosis in Nepalese population. Ninety-one patients with the diagnosis of chronic dermatophytosis of skin willing to participate in the study were recruited in a hospital-based, cross-sectional study. Information regarding demographic profile, health seeking behavior and cost incurred in the treatment of their dermatophytosis were recorded in a preset proforma. Mean age of study population was 30.49±13.50 years with M:F ratio of 2.25:1. Mean duration of illness was 20.68±6.44 months, with groin as the initial site of involvement in nearly half of cases. Commonest diagnoses were extensive dermatophytosis, followed by tinea cruris et corporis and tinea cruris. Nearly three-forth of patients reported seeking advice from local pharmacy and two-third reported using steroid containing topical agents for their skin problem. On an average, patients spent NPR 6,488.70 in a six months period and 3.03% of their income in the treatment of chronic dermatophytosis. This study highlighted the tendency of patients to seek advice from pharmacy dispensers, use of topical steroid containing agents in chronic dermatophytosis and substantial financial burden borne by patients in the treatment of the condition.